Investigating the Prognostic Utility of Serum Osteocalcin and Osteopontin Levels in Predicting Arthroplasty Outcomes - Mohammed, Mohanad Adnan Bakr; Razaq Hamid, Muthanna Abdul; Qaryaqos, Sahar Habeeb (American Journal of Biomedicine and Pharmacy, 2025)
Background: Arthroplasty is a transformative surgical intervention for treating joint disorders and significantly enhances the quality of healthcare. Recent studies have highlighted the role of vitamin K-dependent proteins, including osteocalcin and osteopontin, in bone remodeling and their potential impact on arthroplasty procedures. Objectives: This research study investigates the potential of serum osteocalcin and osteopontin levels as predictive biomarkers for the success of total joint replacement surgeries. Methods: This prospective cohort study involved 50 participants undergoing primary total joint arthroplasty. Patients were divided into two groups based on their arthroplasty outcomes: group A with good outcomes (N=25) and group B with worse outcomes (N=25). Serum osteocalcin and osteopontin levels were measured three months postoperatively, and results were compared between the groups. Results: Serum osteocalcin concentrations were significantly higher in the good outcome group compared to the worse outcome group (21.34±0.92 ng/ml vs. 14.78±2.22 ng/ml, p<0.001). Conversely, serum osteopontin concentrations were significantly lower in the good outcome group compared to the worse outcome group (28.32±1.08 ng/ml vs. 42.15±7.02 ng/ml, p<0.001). Logistic regression analysis confirmed the effectiveness of these biomarkers, with osteocalcin potentially having the most significant impact. Conclusion: Higher serum osteocalcin levels and lower serum osteopontin levels are associated with more favorable arthroplasty outcomes. Monitoring these biomarkers may be an optimal strategy for predicting and managing patient outcomes in joint replacement surgeries.